Shaping the Future of Biological Education Research Selected Papers from the ERIDOB 2022 Conference - Korfiatis, Konstantinos; Grace, Marcus; Hammann, Marcus (Contributions from Biology Education Research,, 2024)
This open access volume is a collection of full papers based on the peer-reviewed presentations accepted for the European Researchers in Didactics of Biology, ERIDOB 2022 conference. ERIDOB aims to bring together researchers in didactics of Biology from Europe and around the world to share and discuss their research work and results. It is the only major international conference whose focus lies exclusively on biology education research, and all the papers are written by international researchers from across Europe (and beyond) which report on a range of contemporary biology education research projects. They are all entirely new papers describing new research in the field. Each paper has been peer-reviewed by experienced biology education researchers and the members of the ERIDOB Academic Committee. The selected papers are collated within the following categories of biology education: · Teaching Strategies and Learning Environments · Students' Knowledge, Conceptions, Values, Attitudes and Motivation · Outdoor and Environmental Education · Biology Teachers' Professional Development By providing a collection of new research findings from many countries, this book is a great resource for researchers and practitioners such as school, college and university biology teachers' around the world. It is useful for training biology teachers and therefore valuable to teacher training institutions.